Adult development and quality of life of transgender and gender nonconforming people. Issue 2 (April 2016) - Bockting, Walter; Coleman, Eli; Deutsch, Madeline B.; Guillamon, Antonio; Meyer, Ilan; Meyer, Walter; Reisner, Sari; Sevelius, Jae; Ettner, Randi
Abstract : Purpose of review: Research on the health of transgender and gender nonconforming people has been limited with most of the work focusing on transition-related care and HIV. The present review summarizes research to date on the overall development and quality of life of transgender and gender nonconforming adults, and makes recommendations for future research. Recent findings: Pervasive stigma and discrimination attached to gender nonconformity affect the health of transgender people across the lifespan, particularly when it comes to mental health and well-being. Despite the related challenges, transgender and gender nonconforming people may develop resilience over time. Social support and affirmation of gender identity play herein a critical role. Although there is a growing awareness of diversity in gender identity and expression among this population, a comprehensive understanding of biopsychosocial development beyond the gender binary and beyond transition is lacking. Summary: Greater visibility of transgender people in society has revealed the need to understand and promote their health and quality of life broadly, including but not limited to gender dysphoria and HIV. This means addressing their needs in context of their families and communities, sexual and reproductive health, and successful aging. Research is needed to better understand what factors are associated with resilience and how it can be effectively promoted.